1996
DOI: 10.1148/radiology.198.3.8628884
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional spiral CT cholangiography in patients with suspected obstructive biliary disease: comparison with endoscopic retrograde cholangiography.

Abstract: Spiral CT cholangiography allows accurate assessment of the biliary system in patients with suspected obstructive biliary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 0 publications
2
53
0
2
Order By: Relevance
“…US has been always considered the first choice technique in the study of biliary obstructive disease, due to its accessibility, speed, ease of performance and low cost [4]. Traditional Computed Tomography (CT) scan is usually considered more accurate than US for helping determine the specific cause and level of obstruction [5]. Both ultrasound and CT scan are regarded as safe and non-invasive procedures in evaluating the status of the biliary tract.…”
mentioning
confidence: 99%
“…US has been always considered the first choice technique in the study of biliary obstructive disease, due to its accessibility, speed, ease of performance and low cost [4]. Traditional Computed Tomography (CT) scan is usually considered more accurate than US for helping determine the specific cause and level of obstruction [5]. Both ultrasound and CT scan are regarded as safe and non-invasive procedures in evaluating the status of the biliary tract.…”
mentioning
confidence: 99%
“…CTVEGB can clearly show the size, configuration, location, surface and base of gallbladder polyps in accordance with color ultrasound, [1][2][3][4][5][6][7] , is capable of detecting biliary calculus, tumor, anomaly and dilatation of the biliary tract and protruding lesions with a bigger size. However, limited by the concentration of contrast medium, small polypous lesions are easily obscured and thus escaping detection by OCCT.…”
Section: Discussionmentioning
confidence: 83%
“…Axial CT data could be reconstructed into two-dimensional multi-planar or three-dimensional (3D) volume-rendered images using workstations and imagerendering software [1] . This CT technology combined with the administration of IV cholangiographic contrast agents could produce diagnostic images of the biliary tract [2][3][4][5][6][7]9,10,14] , and has been used for diagnosis of obstructive biliary disease, choledochocele, choledocholithiasis and aberrance bile ducts. The main limitation of this technique is that the rate of allergic reactions and renal or hepatic toxicity (or both) are relatively high due to by these contrast agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeh et al [46] also found eMRCP inferior to CTCh in visualization of second order bile ducts. Some studies have shown complete agreement between CTCh and endoscopic retrograde cholangiopancreatography [47,48] . MR imaging of the biliary ducts in general is better suited in the evaluation of pathological states wherein biliary ductal dilatation occurs secondary to obstructing calculi or masses [49] while normal caliber bile ducts of potential donors are better demonstrated with CTCh.…”
Section: Biliary Systemmentioning
confidence: 99%